PENERAPAN MODEL QUANTUM TEACHING DALAM MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA PADA SISWA KELAS V MADRASAH IBTIDAIYAH NURUL YAQIN MUARO JAMBI - Putri, Dina; Saidah Ahmad; Arif Wiratama (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to increase motivation to learn mathematics through the use of the Quantum Teaching Learning Model for class V students Madrasah Ibtidaiyah Nurul Yaqin Muaro Jambi, Muaro Jambi Regency. This type of research is a collaborative classroom action research using the Kemmis and Mc Taggart cycle model. The subjects of this study were students of class Madrasah Ibtidaiyah Nurul Yaqin Muaro Jambi, Muaro Jambi Regency. This classroom action research was carried out in 2 cycles. Data collection techniques using observation and questionnaires. The criteria for the success of this action research are the suitability of the teacher to apply the Quantum Teaching learning model and the percentage of student motivation to reach 75%. The results showed that the QuantumTeaching learning model could increase the learning motivation of students in Madrasah Ibtidaiyah Nurul Yaqin Muaro Jambi, Muaro Jambi Regency. The learning is using the TANDUR strategy in the form of facilities from the teacher so that students can grow the strength of AMBAK, get learning experiences, name materials, demonstrate results, repeat material, and celebrate success. In the pre-action, the average student's motivation to learn mathematics obtained a percentage of 60.4%. After being given the action, it increased to 65.5% at the end of the first cycle, and at the end of the second cycle it increased to 77.0%.